PENGEMBANGAN MATERI AJAR PENDIDIKAN AGAMA ISLAM PADA PERGURUAN TINGGI BERBASIS TERJEMAHAN ISTILAH BAHASA ARAB - MIFTAH WANGSADANUREJA (Jurnal Pendidikan Islam, 2017)
The course of Islamic Education (PAI) at the Public University (PTU) for its students seems to be merely a science of knowledge insight only and can not be used as ideological identity in their daily life. This can be proved by the time the author goes around the campus area and finds some students they talks with his fellow students using rough language, such as the phrase "anjrid". Therefore, from the above facts encourage the author to analyze the phenomenon, why the Islamic Education in PTU has not been able to change the character and morals of the students, so the author concluded that one important factor in facing this challenge is to be held back preparation of syllabus and curriculum PAI by looking at student needs analysis at PTU. One such needs analysis is the understanding of Arabic texts contained in the PAI material itself. In this simple article the author use two procedures needs analysis are: 1) collecting learner language samples in the course of PAI through oral and written. 2) Task Analysis After the target task has been identified and the Arabic terms of translation are well researched as the basis for designing Arabic-based PAI materials. Keywords : Materials Development in PAI, Arabic Langguage